VALIDITY OF LEARNING MATTER BASED ON A SCIENTIFIC APPROACH ON CHEMICAL EQUILIBRIUM MATERIAL (UNESA Journal of Chemical Education, 2020)
This study aims to produce a learning matter based on a scientific approach on chemical equilibrium material that is reviewed from the content validity and construct through the results of validation experts. This type of research is a 4-D research model (Define, Design, Develop, and Disseminate) but in this study limited on the development step. The validity results showed that: (1) The content validity obtained valid criteria with average percentage of 80%. (2) The construct validity obtained highly valid criteria with average percentage of 88.7%. From the results, it can be concluded the learning matter based on a scientific approach on chemical equilibrium material was declared valid, reviewed from the content, and construct validity by three validators. Keywords: The Validity, Learning Matter based on a Scientific Approach, Chemical Equilibrium